PENGARUH KEDISIPLINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT GLOBAL BANGUNAN DI KOTA BATAM - Petrus, Petrus; Wangdra, Yvonne (LPPM Universitas Putera Batam, 2020)
The conditions in the globalization era consistently increase and ultimately influence the dicipline, so that strong motivation is needed from the company to all employees so that they continue to provide maximum performance. The purpose of this study is related to the influence of discipline and motivation on the performance of the employees of PT Global Bangunan Seraya in Batam City. The quantitative type of data processed comes from the correspondent's answers regarding the questionnaire and with a total of 118 correspondents. According to the results of the study, the variables derived from discipline and motivation influence the performance variables of employees 18,42 percent and 81,58 percent of other variables. Then occurs or the presence of a positive influence derived from some variables from discipline to the performance variable of the employee with a large enough and occurs or the presence of a positive effect that comes from some variable from the motivation to the performance variable from the employee with a large enough and occurs or the influence which comes from the discipline variable and from the motivation variable simultaneously to the performance variable of the employee with a large enough.